Combined synchrotron x-ray diffraction and NV diamond magnetic microscopy measurements at high pressure - Loïc Toraille; Antoine Hilberer; Thomas Plisson; Margarita Lesik; Mayeul Chipaux; Baptiste Vindolet; Charles Pépin; Florent Occelli; Martin Schmidt; Thierry Debuisschert; Nicolas Guignot; Jean-Paul Itié; et al. (New Journal of Physics, 2020)
We report the possibility to simultaneously perform wide-field nitrogen-vacancy (NV) diamond magnetic microscopy and synchrotron x-ray diffraction measurements at high pressure. NV color centers are created on the culet of a diamond anvil which is integrated in a diamond anvil cell for static compression of the sample. The optically detected spin resonance of the NV centers is used to map the stray magnetic field produced by the sample magnetization. Using this combined scheme, the magnetic and structural behaviors can be simultaneously measured. As a proof-of-principle, we record the correlated α -Fe to ε -Fe structural and magnetic transitions of iron that occur here between 15 and 20 GPa at 300 K.